The predictive value of the prognostic nutritional index for postoperative acute kidney injury in patients undergoing on-pump coronary bypass surgery - Dolapoglu, Ahmet (J Cardiothorac Surg, 2019)
BACKGROUND: We aimed to investigate the predictive value of the prognostic nutritional index (PNI) regarding the development of acute kidney injury (AKI) after elective coronary artery bypass grafting (CABG). METHODS: A total of 336 consecutive patients with normal serum creatinine levels undergoing CABG were enrolled in this retrospective study. AKI was defined as meeting Acute Kidney Injury Network (AKIN) criteria based on the occurrence of creatinine changes within the first 48 h after CABG surgery. The patients were grouped according to whether they developed AKI or not into an AKI (−) and an AKI (+) group. RESULTS: AKI developed in 88 (26.2%) of all patients. The PNI was independently predictive of AKI (OR: 0.829, 95% CI: 0.783–0.877, p <  0.001). Moreover, C-reactive protein (CRP), a history of diabetes mellitus, and positive inotropric usage were independent risk factors for AKI in the multivariate logistic regression analysis. The area under the curve (AUC) of the multivariable model, including positive inotrope support, a history of diabetes mellitus, and CRP, was 0.693 (95% CI: 0.626–0.760, p <  0.001) in predicting AKIN. When the PNI was added to the multivariable model, the AUC was 0.819 (95% CI, 0.762–0.865, z = 3.777, difference p = 0.0002). Also, the addition of the PNI to the multivariable model was associated with a significant net reclassification improvement estimated at 88.2% (p <  0.001) and an integrated discrimination improvement of 0.22 (p <  0.001). CONCLUSIONS: Our study demonstrated that decreasing the PNI could be associated with the development of AKI after coronary artery bypass surgery.